A Sediment Sink for Possible Tertiary Aeolian Sediment in Galway Bay, Western Ireland - Williams, D.; Barham, Milo (Royal Irish Academy, 2012)
There is substantial evidence to suggest that Ireland during the Tertiary Period was subject to a period of intense chemical weathering. Two exposures illustrating this environment in western Ireland are described, adding to the known examples of this type of weathering elsewhere in Ireland. The surface features of quartz sand grains may be used to distinguish the environments through which they have passed during transport and deposition. Quartzgrain surface features photographed by a scanning electron microscope are described from a sediment facies, ~10,000 years old, retrieved from cores taken from beneath the floor of Galway Bay. Many of these show the action of glacial activity by characteristic fracture patterns, as might be expected in Holocene sediment in an Irish context. Some of the grains, however, show features that suggest a prior aeolian component to their transport history. These grains are compared with quartz grains previously described and with the product of Tertiary Period weathering recovered from a sand pit at Pollnahallia, Co. Galway. Similarities suggest that some of the sand grains found at depths of ~2-5m beneath the substrate surface of Galway Bay may have originated from chemical weathering and aeolian transport during the late Tertiary Period and then been reworked in glacial and subsequent deltaic environments.